Self-Control Behavior with An Approach Theory of Planned Behavior in Managing Finance for MSME - Panjaitan, Thyophoida Wanty Suryani; Wisyastuti, Maria; Hermanto, Yustinus Budi (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The aim of the research is to analyze the factors that influence the self-control behavior of MSME actors in financial management and to determine the factors that influence the intentions of MSME actors in controlling themselves in financial management by applying the theory of planned behavior. Design/methodology/approach: This research is quantitative. The population is MSMEs in Malang, Gresik, Pasuruan, Sidoarjo, and Surabaya, with a sample size of 200 MSMEs operating as of December 2022. Data collection used a questionnaire. Findings: The results obtained indicate that power prestige and retention-time influence the intention to perform self-control behavior; subjective norms do not influence the intention to perform self-control behavior; behavior control influences the intention to perform self-control behavior; power prestige, behavior control, and intention to perform self-control behavior influence self-control behavior. Meanwhile, retention-time and subjective norms influence self-control behavior. Research limitations/implications: Respondent data collection was only from several cities in East Java, namely Malang, Gresik, Pasuruan, Sidoarjo, and Surabaya.. Practical implications: MSMEs can manage their finances, exercise self-control, evaluate, and use funds effectively, while avoiding wasteful behavior. Originality/value: Discusses theoretical approaches and practical benefits in MSME financial management. Paper type: Research paper